2020
DOI: 10.1039/d0ta08752a
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the origin of the photocarrier dynamics of fullerene-derivative passivation of SnO2 electron transporters in perovskite solar cells

Abstract: Fullerene-passivated SnO2 electron transport layers (ETLs) offer the route for continued boost in power conversion efficiencies (PCEs) of perovskite solar cells (PSCs). However, the detailed understanding on the photocarrier dynamics...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 47 publications
1
30
0
Order By: Relevance
“…In the monolayer of SnO 2 , additive is employed to achieve this aim. Same as the TiO 2 , the additive using in SnO 2 includes metal ion (e.g., Li + , 422 Mg 2+ , 423,424 Eu 3+ , 397 Y 3+ , 425 Zr 4+ , 426 Nb 5+ 427,428 ), function material (e.g., TiCl 4 , 429 KCl, 430 RbF, 393 Eu‐WO x , 431 MXene, 394,432,433 NH 4 F, 403 CdS, 434 phosphoric acid, 435 , 435 g‐C 3 N 4 , 436 EDTA, 437 ionic liquid, 406 SPF, 438 PEG, 439 graphene, 440 carbon, 441,442 fullerene and its derivatives, 443–446 ) and plasma gas (e.g., N 2 , 447 Ar and O 2 448 ). For example, Park et al 422 demonstrated that Li + can enhance the conductivity and induce a downward shift of HOMO and LUMO of SnO 2 , which facilitated injection and transfer of electrons from t MAPbI 3 perovskite to SnO 2 .…”
Section: Carrier Engineeringmentioning
confidence: 99%
“…In the monolayer of SnO 2 , additive is employed to achieve this aim. Same as the TiO 2 , the additive using in SnO 2 includes metal ion (e.g., Li + , 422 Mg 2+ , 423,424 Eu 3+ , 397 Y 3+ , 425 Zr 4+ , 426 Nb 5+ 427,428 ), function material (e.g., TiCl 4 , 429 KCl, 430 RbF, 393 Eu‐WO x , 431 MXene, 394,432,433 NH 4 F, 403 CdS, 434 phosphoric acid, 435 , 435 g‐C 3 N 4 , 436 EDTA, 437 ionic liquid, 406 SPF, 438 PEG, 439 graphene, 440 carbon, 441,442 fullerene and its derivatives, 443–446 ) and plasma gas (e.g., N 2 , 447 Ar and O 2 448 ). For example, Park et al 422 demonstrated that Li + can enhance the conductivity and induce a downward shift of HOMO and LUMO of SnO 2 , which facilitated injection and transfer of electrons from t MAPbI 3 perovskite to SnO 2 .…”
Section: Carrier Engineeringmentioning
confidence: 99%
“…New studies in this scope are insightful and welcome. The study of alternative electron collecting materials such as SnO 2 and fullerene‐passivated SnO 2 [ 148,154–158 ] or even the organic [6,6]‐phenyl‐C61‐butyric acid methyl ester (PCBM) [ 159–162 ] are other possible ways in which further research can be carried out. They already presented the first results for PQDs [ 51 ] and are inevitable tendencies for research.…”
Section: Pqd Solar Cell Architecturesmentioning
confidence: 99%
“…The spin-coated fullerene derivative film is widely used as an electron transport layer in perovskite solar cells. Polar fullerene derivatives, such as [6,6]-phenyl-C 61 -butyric acid methyl ester (PCBM) and C 60 pyrrolidine tris-acid (CPTA), can be used for interface engineering in perovskite solar cells. ,, Because fullerene derivatives electrically couple with oxide surfaces to effectively modify the work function, they dramatically improved the efficiency of perovskite solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we describe our use of a CPTA spin-coating process and an EBL preset to realize a two-terminal nanoscale switching device. After the spin coating, the CPTA was vertically anchored to the bottom oxide substrate by their carboxylic acid groups, ,, to ensure that there were no horizontal connections between CPTA molecules. Thus, the initial CPTA film exhibited a highly resistivity in-plane conduction measurement.…”
Section: Introductionmentioning
confidence: 99%